A SPATIAL DECISION SUPPORT SYSTEM (SDSS) FOR SUSTAINABLE TOURISM PLANNING IN CAMERON l l!Gl-ILANDS, MALAYSIA - ,, MANSIR AMINU (2014)
Sustainable approach to tourism development 1s rarely addressed among the academicians, the authorities and the participants, as well as the usc of tools which will guide the decision environment in evaluation and planning. This research presents an approach based on an integrated use of Geographic Information System (GIS). Analytic Network Process (ANI') and Water Quality Index (WQJ) for sustainable tourism planning in Cameron Highlands. Malaysia. ANP was utilized to evaluate the relative priorities tor the sustainable tourism development of the highlands based on chosen criteria and indicators (elements). Pair wise comparison technique was used in order to evaluate possible alternatives from different perspective VCs. This was achieved through the assignment of weight to each criteria that indicates its importance relatively to the other under consideration using expert opinion as input. The results were then transferred into GIS environment.